A highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable and a preparation method thereof
By using the synergistic effect of multiple materials in the drag chain cable, the problems of insufficient wear resistance, flame retardant and weather resistance of existing cables are solved, and the comprehensive performance of high wear resistance, flame retardant, weather resistance and bending resistance are achieved, extending service life and reducing safety hazards.
Patent Information
- Application Number
- CN202411562240.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The existing drag chain cables have poor wear resistance, flame retardant and weather resistance during friction and stretching, resulting in short service life and safety hazards.
Materials such as nitrile rubber, polyvinyl chloride resin, polystyrene-polybutadiene-polystyrene copolymer, polyisobutylene, composite flame retardant, modified reinforced microspheres, modified nanotitanium dioxide, ultraviolet absorbers and coupling agents are used to improve the flame retardant performance, wear resistance, weather resistance and bending resistance of the cable through synergistic action.
It achieves comprehensive performance of high wear resistance, flame retardant, weather resistance and bending resistance, extends the service life of the cable, reduces safety hazards, and has a wide market application prospect.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the field of cable technology, and in particular to a highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable and a preparation method thereof. Background Art
[0002] In order to meet more application scenarios of cables, such as during car charging, the cable needs to be removed from the charging pile and dragged to the car charging port for charging. During the movement of the cable, the cable will inevitably rub against the ground. At the same time, the cable itself will also produce tensile deformation during the dragging process. If the cable itself has poor wear resistance, flame retardancy, weather resistance and tensile resistance, it will not only reduce the service life of the cable and the stability of electrical performance, but may also pose a safety hazard.
[0003] Therefore, a drag chain cable with high wear resistance, excellent flame retardant performance, good weather resistance and tensile resistance is developed to meet the needs of the high-end market. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present application provides a highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cable and a preparation method thereof. The highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cable of the present application has excellent flame retardancy, wear resistance, weather resistance and bending resistance. At the same time, it has a wide market application prospect.
[0005] In the first aspect, the present application provides a highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable, which adopts the following technical solutions:
[0006] A highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cable comprises an outer protective sheath, wherein the outer protective sheath is prepared from the following raw materials, measured by weight: 50-55 parts of nitrile rubber, 10-12 parts of polyvinyl chloride resin, 7-9 parts of polystyrene-polybutadiene-polystyrene copolymer, 4-6 parts of polyisobutylene, 3-4 parts of composite flame retardant, 20-22 parts of modified reinforced microspheres, 20-24 parts of modified nano titanium dioxide, 0.2-0.3 parts of ultraviolet absorber and 1-2 parts of coupling agent, wherein the composite flame retardant consists of graphene-modified 2-carboxyethylphenyl hypophosphite and rare earth flame retardant.
[0007] By adopting the above technical scheme, the highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cable of the present application achieves excellent flame retardant performance, wear resistance, weather resistance and bending resistance through the synergistic effect of each component. Specifically: Nitrile rubber, as the main material of the outer protective sheath, provides good mechanical strength and wear resistance. Polyvinyl chloride resin and polystyrene-polybutadiene-polystyrene copolymer jointly improve the weather resistance of the material. The composite flame retardant is composed of graphene-modified 2-carboxyethylphenyl hypophosphorous acid and rare earth flame retardant, wherein graphene-modified 2-carboxyethylphenyl hypophosphorous acid improves the flame retardant effect, forms a foam layer to release non-flammable gas, and dilutes the oxygen in the environment; rare earth flame retardant forms a stable compound at high temperature, isolates oxygen, and slows down the burning rate of the material. The synergistic effect of the two significantly improves the flame retardant performance of the outer protective sheath. The modified reinforced microspheres are obtained by dimethylbisindenylsilane, magnesium sulfate whiskers and mica powder to obtain mica powder loaded materials, and then coated with polyurethane on the outside to obtain modified reinforced microspheres. Magnesium sulfate whiskers have high strength, rigidity, wear resistance and weather resistance, and can increase the strength, wear resistance and rigidity of the outer protective sheath of the highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cable; dimethyl diindenyl silane is fully cross-linked with the other components of the outer protective sheath to form a complete and tight network structure, so that the highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cable can withstand greater force when subjected to external tensile stress, reducing the damage caused by stretching; mica powder is loaded to achieve a better dispersion effect, so that dimethyl diindenyl silane and magnesium sulfate whiskers can achieve a synergistic effect while maintaining their unique properties. Modified nano titanium dioxide has a strong UV shielding effect, and has excellent wear resistance and antioxidant properties, which can effectively avoid chemical corrosion and UV radiation of the cable, thereby improving the aging resistance and wear resistance of the cable. The UV absorber can absorb solar ultraviolet radiation, prevent ultraviolet rays from irradiating and damaging the material of the outer protective sheath of the highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cable, reduce the aging rate of the material of the outer protective sheath, and extend the service life of the material of the outer protective sheath. In summary, the highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable of the present application achieves excellent comprehensive performance through the synergistic effect of various components and has broad market application prospects.
[0008] Preferably, the mass ratio of the graphene-modified 2-carboxyethylphenyl hypophosphorous acid to the rare earth flame retardant is 5:3.
[0009] By adopting the above technical solution, the mass ratio of graphene-modified 2-carboxyethylphenyl hypophosphorous acid and rare earth flame retardant is 5:3. This ratio design enables the two materials to play a synergistic role in the outer protective sheath, thereby improving the flame retardant performance, wear resistance, weather resistance and bending resistance of the cable. Graphene-modified 2-carboxyethylphenyl hypophosphorous acid plays a key role as a flame retardant in the outer protective sheath. It can improve the flame retardant effect, enhance compatibility and dispersibility, form a three-dimensional network structure, and work together with rare earth flame retardants to improve the flame retardant performance of the outer protective sheath and improve the comprehensive performance of the outer protective sheath. Rare earth flame retardants may form stable compounds at high temperatures, thereby forming a protective layer during the combustion process, isolating oxygen and slowing down the burning rate of the material. When combined with graphene-modified 2-carboxyethylphenyl hypophosphorous acid, the overall flame retardant effect can be enhanced and the flame retardant performance of the outer protective sheath can be improved. At the same time, rare earth compounds generally have good thermal stability, which helps to improve the performance of the outer protective sheath in high temperature environments and reduce thermal degradation. Therefore, by rationally selecting the mass ratio of graphene-modified 2-carboxyethylphenylphosphite and rare earth flame retardant to be 5:3, the two materials can play a synergistic role in the outer protective sheath layer, thereby improving the overall performance of the cable.
[0010] Preferably, the method for preparing the graphene-modified 2-carboxyethylphenyl hypophosphorous acid comprises the following steps:
[0011] S31, dispersing 100 parts of 2-carboxyethylphenylphosphite and 20 parts of graphene oxide in a solution consisting of 15 parts of γ-aminopropyltrimethoxysilane, 200 parts of ethanol and 25 parts of water according to parts by mass to obtain a mixed solution;
[0012] S32, heating the mixed solution to 48°C, stirring at a rate of 500 rpm, reacting for 400 min, filtering, and vacuum drying at 73°C for 24 h, grinding and sieving to obtain graphene-modified 2-carboxyethylphenyl hypophosphorous acid with a particle size of 2-5 μm.
[0013] By adopting the above technical scheme, the prepared graphene-modified 2-carboxyethylphenyl hypophosphorous acid plays a key role. As a gas source, it promotes the flame retardant to form a foam layer, releases a large amount of non-flammable gas, dilutes the oxygen in the environment, and thus improves the flame retardant effect. At the same time, through the modification of γ-aminopropyltrimethoxysilane, it helps the combination between graphene and 2-carboxyethylphenyl hypophosphorous acid, enhances the interaction between them, and improves the compatibility and dispersibility in the outer protective sheath. In addition, graphene oxide forms a three-dimensional network structure, which further enhances the flame retardant effect of the composite paper core. Finally, the graphene-modified 2-carboxyethylphenyl hypophosphorous acid and the rare earth flame retardant work together to further improve the flame retardant properties and comprehensive properties of the outer protective sheath.
[0014] Preferably, the preparation method of the rare earth flame retardant is: add 4 mol of aminotrimethylenephosphonic acid and 1.5 mol of cerium nitrate into a hydrothermal reactor, add 200 mL of deionized water as a solvent, and add 0.15 mol of lithium nitrate, heat to 155-165° C., react for 30-36 hours, and obtain the rare earth flame retardant.
[0015] By adopting the above technical solution, the rare earth flame retardant prepared, the rare earth element cerium usually has special chemical properties, and may form a stable compound at high temperature, thereby forming a protective layer during the combustion process, isolating oxygen and slowing down the burning speed of the material. The rare earth flame retardant is combined with graphene-modified 2-carboxyethylphenyl hypophosphorous acid to synergistically enhance the overall flame retardant effect and improve the flame retardant performance of the outer protective sheath.
[0016] Preferably, the method for preparing the modified reinforced microspheres comprises the following steps:
[0017] S51, according to the mass fractions, 1.5 parts of dimethylbisindenylsilane and 9 parts of ethanol were mixed to obtain a solution A, 3 parts of magnesium sulfate whiskers with a diameter of 3-5 μm and an aspect ratio of 10-12 and 5 parts of mica powder with a particle size of 5 microns were dispersed in 10 parts of deionized water to obtain a solution B, and the solution A was slowly added to the solution B, and after ultrasonic mixing, the solution was added to a hydrothermal reactor for treatment for 50-60 minutes. After the reaction was completed, the solution was filtered, washed, and dried to obtain a mica-loaded material;
[0018] S52. According to the mass fractions, 6 parts of mica-loaded material were dispersed in 40 parts of ether to obtain solution C, 6 parts of polyurethane were dissolved in 30 parts of dichloromethane to obtain solution D, 0.07 parts of dibutyltin dilaurate were added to solution D, and then solution C was slowly added. After reacting for 6-7 hours, the solid was filtered out, washed, and vacuum dried at 130°C to obtain modified reinforced microspheres.
[0019] By adopting the above technical scheme, in the preparation of modified reinforced microspheres, dimethyldiindenylsilane, magnesium sulfate whisker and mica powder are used to obtain a mica powder loading material, and then polyurethane is coated on the outside to obtain modified reinforced microspheres. The magnesium sulfate whisker has high strength, rigidity, wear resistance and weather resistance, and can increase the strength, wear resistance and rigidity of the outer protective sheath of the highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cable. Dimethyldiindenylsilane is fully cross-linked with the other components of the outer protective sheath to form a complete and tight network structure, making the highly wear-resistant, flame-retardant and weather-resistant drag chain cable The flame-retardant, weather-resistant and tensile-resistant drag chain cable can withstand greater force when subjected to external tensile stress, reducing damage caused by stretching. It also has good weather resistance, effectively preventing aging and degradation of the outer protective sheath. Mica powder is used for loading to achieve better dispersion effect, so that dimethylbisindenylsilane and magnesium sulfate whiskers can achieve synergistic effects while maintaining their unique properties. The outer protective sheath not only retains the stability, resilience and weather resistance of polyurethane, but also enhances the flame retardant effect, wear resistance and bending resistance.
[0020] Preferably, the preparation method of the modified nano titanium dioxide is as follows: according to the mass fractions, 10 parts of nano titanium dioxide are uniformly dispersed in 60 parts of anhydrous ethanol, and then 0.3 parts of hexamethyldisilazane, 0.2 parts of stearic acid, 0.15 parts of isomeric tridecanol polyoxyethylene ether, and 0.1 parts of vinyltrimethoxysilane are added, the temperature condition is maintained at 40°C, ultrasonic stirring is first performed for 50 minutes, ultrasonic cleaning is performed for 30 minutes, and then magnetic stirring is performed for 3 hours, and then centrifugation, separation, washing, and drying are performed to obtain the modified nano titanium dioxide.
[0021] By adopting the above technical solution, nano titanium dioxide itself has a strong UV shielding effect, and has excellent wear resistance and antioxidant properties, which can effectively avoid chemical corrosion and UV radiation of the cable, thereby improving the aging resistance and wear resistance of the cable. However, conventional nano titanium dioxide is hydrophilic, and has poor dispersibility and compatibility, and it is difficult to disperse evenly in the outer protective sheath. Through modification with isomeric tridecanol polyoxyethylene ether and vinyl trimethoxysilane, its dispersibility and compatibility are significantly improved, thereby significantly improving the wear resistance, weather resistance and bending resistance of the cable.
[0022] Preferably, the ultraviolet absorber is composed of dioctadecyl pentaerythritol phosphate and BASF light stabilizer CHIMASSORB944 in a mass ratio of 3:4.
[0023] By adopting the above technical scheme, the ultraviolet absorber can absorb solar ultraviolet radiation, prevent ultraviolet rays from irradiating and damaging the materials of the outer protective sheath of the highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable, reduce the aging speed of the materials of the outer protective sheath, and extend the service life of the materials of the outer protective sheath. The synergistic effect between the ultraviolet absorber composed of dioctadecyl pentaerythritol phosphate and BASF light stabilizer CHIMASSORB944 can more effectively absorb ultraviolet rays and improve the comprehensive performance of the materials of the outer protective sheath.
[0024] Preferably, the coupling agent is composed of vinyltrimethoxysilane and γ-glycidyloxypropyltrimethoxysilane in a mass ratio of 3:4.
[0025] By adopting the above technical scheme, the coupling agent plays a very important role in the preparation of highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cables. The coupling agent composed of vinyl trimethoxysilane and γ-glycidyl ether oxypropyl trimethoxysilane in a mass ratio of 3:4 can effectively improve the compatibility and bonding between the components of the outer protective sheath layer and improve the overall performance of the cable. Vinyl trimethoxysilane has good adhesion and reactivity, and can form chemical bonds with polymer materials, thereby enhancing the interfacial bonding strength between the outer protective sheath layer and the filler. γ-glycidyl ether oxypropyl trimethoxysilane can form a hydrophobic layer on the surface of the material, improve the water resistance and weather resistance of the material, and also increase the wear resistance and bending resistance of the material. The synergistic effect between vinyl trimethoxysilane and γ-glycidyl ether oxypropyl trimethoxysilane enables the outer protective sheath layer to have better processing performance and service life while maintaining excellent performance. The use of this coupling agent not only improves the overall performance of the cable, but also reduces the production cost, and has broad market application prospects.
[0026] Preferably, the acrylonitrile content of the nitrile rubber is 34-37%; the K value of the polyvinyl chloride resin is 63-65; the polyisobutylene is BASF Oppanol B50 type, and the number average molecular weight is 120,000.
[0027] In a second aspect, the present application provides a method for preparing a highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable, using the following technical solution:
[0028] As a general technical concept, the present application also provides a method for preparing the above-mentioned highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable. According to the mass fractions, nitrile rubber, polyvinyl chloride resin, polystyrene-polybutadiene-polystyrene copolymer, polyisobutylene, composite flame retardant, modified reinforcing microspheres, modified nano titanium dioxide, ultraviolet absorber and coupling agent are added in sequence to a high-speed mixer for pre-mixing and mixing. The mixing temperature is 120-125°C for 30 minutes, and the mixture is cooled to 80°C. The mixture is then extruded and granulated through a twin-screw extruder. The extrusion temperature is 170-180°C and the screw speed is 120rpm to obtain the material of the outer protective sheath layer of the highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable.
[0029] In summary, the present application includes at least one of the following beneficial technical effects:
[0030] 1. Excellent comprehensive performance: Through reasonable formula design and raw material selection, the prepared drag chain cable has excellent flame retardant properties, wear resistance, weather resistance and bending resistance, meeting the needs of different application scenarios.
[0031] 2. Good UV protection effect: The combination of UV absorber and modified nano titanium dioxide can effectively prevent UV damage to the outer protective sheath of the cable, reduce the aging speed of the material and extend the service life.
[0032] 3. Improve compatibility and dispersibility: Through the use of modified reinforcing microspheres and coupling agents, the interaction between graphene-modified 2-carboxyethylphenyl hypophosphorous acid and rare earth flame retardant is improved, as well as the dispersibility and compatibility of nano-titanium dioxide in the outer protective sheath of the cable, further improving the comprehensive performance of the cable.
[0033] 4. Significant synergistic effect: Graphene-modified 2-carboxyethylphenyl hypophosphorous acid and rare earth flame retardant work together to improve the flame retardant properties of the outer protective sheath and enhance the overall performance of the outer protective sheath.
[0034] 5. Broad application prospects: Due to its excellent comprehensive performance, the drag chain cable can be widely used in electric power, petroleum, chemical industry, metallurgy and other fields, and has broad market application prospects. DETAILED DESCRIPTION
[0035] The following will describe the implementation scheme of the present application in detail with reference to the examples, but those skilled in the art will understand that the following examples are only used to illustrate the present application and should not be considered to limit the scope of the present application. If the specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially. In the examples, preparation examples and comparative examples: polystyrene-polybutadiene-polystyrene copolymers were purchased from SINOPEC (Hunan, China), wherein the styrene content was 30.1wt%; the acrylonitrile content of the nitrile rubber was 34%; the polyvinyl chloride resin was SG-6 type, a polyvinyl chloride resin with a K value of 63-65; polyisobutylene was BASF Oppanol B50 type, with a number average molecular weight of 120,000, and 100g per 1 portion.
[0036] Preparation Example 1 Preparation of graphene-modified 2-carboxyethylphenyl hypophosphorous acid
[0037] The preparation method of graphene-modified 2-carboxyethylphenyl hypophosphorous acid comprises the following steps:
[0038] S31, dispersing 100 parts of 2-carboxyethylphenylphosphite and 20 parts of graphene oxide in a solution consisting of 15 parts of γ-aminopropyltrimethoxysilane, 200 parts of ethanol and 25 parts of water according to parts by mass to obtain a mixed solution;
[0039] S32, heating the mixed solution to 48°C, stirring at a rate of 500 rpm, reacting for 400 min, filtering, and vacuum drying at 73°C for 24 h, grinding and sieving to obtain graphene-modified 2-carboxyethylphenyl hypophosphorous acid with a particle size of 2-5 μm.
[0040] Preparation Example 2 Preparation of rare earth flame retardant
[0041] The preparation method of the rare earth flame retardant is as follows: 4 mol of aminotrimethylenephosphonic acid and 1.5 mol of cerium nitrate are added into a hydrothermal reactor, 200 mL of deionized water is added as a solvent, and 0.15 mol of lithium nitrate is added at the same time, the temperature is raised to 160° C., and the reaction time is 33 hours to obtain the rare earth flame retardant.
[0042] Preparation Example 3 Preparation of modified reinforced microspheres
[0043] The preparation method of modified reinforced microspheres comprises the following steps:
[0044] S51, according to the mass fractions, 1.5 parts of dimethylbisindenylsilane and 9 parts of ethanol were mixed to obtain a solution A, 3 parts of magnesium sulfate whiskers with a diameter of 3-5 μm and an aspect ratio of 10-12 and 5 parts of mica powder with a particle size of 5 microns were dispersed in 10 parts of deionized water to obtain a solution B, and the solution A was slowly added to the solution B, and after ultrasonic mixing, the solution was added to a hydrothermal reactor for treatment for 55 minutes. After the reaction was completed, the solution was filtered, washed, and dried to obtain a mica-loaded material;
[0045] S52. According to the mass proportions, 6 parts of mica-loaded material were dispersed in 40 parts of ether to obtain solution C, 6 parts of polyurethane were dissolved in 30 parts of dichloromethane to obtain solution D, 0.07 parts of dibutyltin dilaurate were added to solution D, and then solution C was slowly added. After reacting for 6.5 hours, the solid was filtered out, washed, and vacuum dried at 130°C to obtain modified reinforced microspheres.
[0046] Preparation Example 4 Preparation of modified nano-titanium dioxide
[0047] The preparation method of modified nano titanium dioxide is as follows: according to the mass fraction, 10 parts of nano titanium dioxide are uniformly dispersed in 60 parts of anhydrous ethanol, and then 0.3 parts of hexamethyldisilazane, 0.2 parts of stearic acid, 0.15 parts of isomeric tridecanol polyoxyethylene ether, and 0.1 parts of vinyltrimethoxysilane are added, and the temperature condition is maintained at 40°C, first ultrasonically stirred for 50 minutes, ultrasonically cleaned for 30 minutes, and then magnetically stirred for 3 hours, and then centrifuged, separated, washed, and dried to obtain modified nano titanium dioxide. Example 1
[0048] A highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cable comprises an outer protective sheath, wherein the outer protective sheath is prepared from raw materials comprising, by weight, 50 parts of nitrile rubber, 10 parts of polyvinyl chloride resin, 7 parts of polystyrene-polybutadiene-polystyrene copolymer, 4 parts of polyisobutylene, 3 parts of a composite flame retardant, 20 parts of modified reinforcing microspheres, 20 parts of modified nano titanium dioxide, 0.2 parts of an ultraviolet absorber, and 1 part of a coupling agent, wherein the composite flame retardant is composed of graphene-modified 2-carboxyethylphenyl hypophosphite and a rare earth flame retardant in a weight ratio of 5:3, the ultraviolet absorber is composed of dioctadecyl pentaerythritol phosphate and BASF light stabilizer CHIMASSORB944 in a weight ratio of 3:4, and the coupling agent is composed of vinyl trimethoxy silane and γ-glycidyl ether oxypropyl trimethoxy silane in a weight ratio of 3:4.
[0049] The preparation method of the above-mentioned highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable is as follows: nitrile rubber, polyvinyl chloride resin, polystyrene-polybutadiene-polystyrene copolymer, polyisobutylene, composite flame retardant, modified reinforcing microspheres, modified nano titanium dioxide, ultraviolet absorber and coupling agent are added in sequence in accordance with their mass fractions into a high-speed mixer for premixing and mixing. The mixing temperature is 120°C for 30 minutes, and the mixture is cooled to 80°C. The mixture is then extruded and granulated through a twin-screw extruder. The extrusion temperature is 170°C and the screw speed is 120rpm to obtain the material of the outer protective sheath layer of the highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable. Example 2
[0050] A highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cable comprises an outer protective sheath, wherein the outer protective sheath is prepared from raw materials comprising, by weight: 55 parts of nitrile rubber, 12 parts of polyvinyl chloride resin, 9 parts of polystyrene-polybutadiene-polystyrene copolymer, 6 parts of polyisobutylene, 4 parts of a composite flame retardant, 22 parts of modified reinforcing microspheres, 24 parts of modified nano titanium dioxide, 0.3 parts of an ultraviolet absorber, and 2 parts of a coupling agent, wherein the composite flame retardant is composed of graphene-modified 2-carboxyethylphenyl hypophosphorous acid and a rare earth flame retardant in a weight ratio of 5:3, the ultraviolet absorber is composed of dioctadecyl pentaerythritol phosphate and BASF light stabilizer CHIMASSORB944 in a weight ratio of 3:4, and the coupling agent is composed of vinyl trimethoxy silane and γ-glycidyl ether oxypropyl trimethoxy silane in a weight ratio of 3:4.
[0051] The preparation method of the above-mentioned highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable is as follows: nitrile rubber, polyvinyl chloride resin, polystyrene-polybutadiene-polystyrene copolymer, polyisobutylene, composite flame retardant, modified reinforcing microspheres, modified nano titanium dioxide, ultraviolet absorber and coupling agent are added in sequence to a high-speed mixer for premixing and mixing according to their mass fractions. The mixing temperature is 125°C for 30 minutes, and the mixture is cooled to 80°C. The mixture is then extruded and granulated through a twin-screw extruder. The extrusion temperature is 180°C and the screw speed is 120rpm to obtain the material of the outer protective sheath layer of the highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable. Example 3
[0052] A highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cable comprises an outer protective sheath, wherein the outer protective sheath is prepared from raw materials comprising, by weight: 53 parts of nitrile rubber, 11 parts of polyvinyl chloride resin, 8 parts of polystyrene-polybutadiene-polystyrene copolymer, 5 parts of polyisobutylene, 3.5 parts of a composite flame retardant, 21 parts of modified reinforcing microspheres, 22 parts of modified nano titanium dioxide, 0.25 parts of an ultraviolet absorber, and 1.5 parts of a coupling agent, wherein the composite flame retardant is composed of graphene-modified 2-carboxyethylphenyl hypophosphorous acid and a rare earth flame retardant in a weight ratio of 5:3, the ultraviolet absorber is composed of dioctadecyl pentaerythritol phosphate and BASF light stabilizer CHIMASSORB944 in a weight ratio of 3:4, and the coupling agent is composed of vinyl trimethoxy silane and γ-glycidyl ether oxypropyl trimethoxy silane in a weight ratio of 3:4.
[0053] The preparation method of the above-mentioned highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable is as follows: nitrile rubber, polyvinyl chloride resin, polystyrene-polybutadiene-polystyrene copolymer, polyisobutylene, composite flame retardant, modified reinforcing microspheres, modified nano titanium dioxide, ultraviolet absorber and coupling agent are added in sequence in accordance with their mass fractions into a high-speed mixer for premixing and mixing. The mixing temperature is 123°C for 30 minutes, and the mixture is cooled to 80°C. The mixture is then extruded and granulated through a twin-screw extruder. The extrusion temperature is 175°C and the screw speed is 120rpm to obtain the material of the outer protective sheath layer of the highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable.
[0054] Comparative Example 1
[0055] The same as Example 3, except that: the composite flame retardant is graphene-modified 2-carboxyethylphenyl hypophosphorous acid.
[0056] Comparative Example 2
[0057] The same as Example 3, except that: the composite flame retardant is a rare earth flame retardant.
[0058] Comparative Example 3
[0059] The same as Example 3, except that: the ultraviolet absorber is dioctadecyl pentaerythritol phosphate.
[0060] Comparative Example 4
[0061] The same as Example 3, except that: the ultraviolet absorber is BASF light stabilizer CHIMASSORB944.
[0062] Comparative Example 5
[0063] The same as Example 3, except that: the coupling agent is vinyltrimethoxysilane.
[0064] Comparative Example 6
[0065] The same as Example 3, except that: the coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0066] Comparative Example 7
[0067] The same as Example 3, except that an equal amount of nano titanium dioxide is used instead of modified nano titanium dioxide.
[0068] Comparative Example 8
[0069] The same as Example 3, except that the amount of modified reinforcing microspheres added is 0 parts.
[0070] Performance testing
[0071] The materials of the outer protective sheath layer of the highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cables prepared in Examples 1 to 3 and Comparative Examples 1 to 8 were sampled and the following tests were performed;
[0072] The tensile strength and flame retardant properties are tested according to the standard GB / T32129-2015 "Halogen-free and low-smoke flame-retardant cable materials for wires and cables";
[0073] Abrasion resistance is tested according to ISO 4649:2017;
[0074] The above test results are shown in Table 1;
[0075] Aging test: The materials of the outer protective sheath of the highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cables prepared in each embodiment and comparative example were subjected to an air oven aging test using an XL-016A ventilation aging box at a temperature of (150±2)°C for 168 hours to test the maximum change rate of tensile strength and the maximum change rate of elongation at break.
[0076] Weathering test: The LQ-UV1-S type anti-ultraviolet durability test chamber was used to conduct an anti-ultraviolet test on the materials of the outer protective sheath layer of the highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cables prepared in each embodiment and comparative example, at a temperature of (40±2)°C and a time of 720h, and the maximum change rate of tensile strength and the maximum change rate of elongation at break were tested;
[0077] The above test results are shown in Table 2.
[0078] Table 1 Test results of mechanical properties, wear resistance and flame retardancy
[0079]
[0080] Table 2 Aging resistance and weathering test results
[0081]
[0082] Analyzing the data in Tables 1 and 2, we can see that:
[0083] 1) Example 1-Example 3 The material of the outer protective sheath layer of the highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable of the present application has excellent flame retardancy, wear resistance, weather resistance and bending resistance, and has broad market application prospects.
[0084] 2) A comparative analysis of the performance of the materials of the outer protective sheath of the highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable prepared in combination with Example 3 and Comparative Examples 1-2 shows that the mass ratio of the graphene-modified 2-carboxyethylphenyl hypophosphite and the rare earth flame retardant is 5:3, and the synergistic effect between the graphene-modified 2-carboxyethylphenyl hypophosphite and the rare earth flame retardant is utilized to improve the flame retardant properties, wear resistance, weather resistance and bending resistance of the cable.
[0085] 3) The performance comparison analysis of the materials of the outer protective sheath of the highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cable prepared in combination with Example 3 and Comparative Examples 3-4 shows that the ultraviolet absorber is composed of dioctadecyl pentaerythritol phosphate and BASF light stabilizer CHIMASSORB944 in a mass ratio of 3:4. The ultraviolet absorber can absorb solar ultraviolet radiation, prevent ultraviolet rays from irradiating and damaging the materials of the outer protective sheath of the highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cable, reduce the aging speed of the materials of the outer protective sheath, and extend the service life of the materials of the outer protective sheath. The synergistic effect between the ultraviolet absorbers composed of dioctadecyl pentaerythritol phosphate and BASF light stabilizer CHIMASSORB944 can more effectively absorb ultraviolet rays and improve the comprehensive performance of the materials of the outer protective sheath.
[0086] 4) The performance comparison analysis of the materials of the outer protective sheath of the highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cable prepared in Example 3 and Comparative Examples 5-6 shows that the coupling agent is composed of vinyl trimethoxysilane and γ-glycidyl ether oxypropyl trimethoxysilane in a mass ratio of 3:4. The synergistic effect between vinyl trimethoxysilane and γ-glycidyl ether oxypropyl trimethoxysilane is utilized to make the outer protective sheath have better processing performance and service life while maintaining excellent performance. The use of this coupling agent not only improves the overall performance of the cable, but also reduces the production cost, and has broad market application prospects.
[0087] 5) The performance comparison analysis of the materials of the outer protective sheath of the highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cable prepared in combination with Example 3 and Comparative Example 7 shows that nano titanium dioxide itself has a strong ultraviolet shielding effect, and has excellent wear resistance and antioxidant properties, which can effectively avoid chemical corrosion and ultraviolet radiation of the cable, thereby improving the aging resistance and wear resistance of the cable. However, conventional nano titanium dioxide is hydrophilic, has poor dispersibility and compatibility, and is difficult to be evenly dispersed in the outer protective sheath. The present application prepares modified nano titanium dioxide by modification with isomeric tridecanol polyoxyethylene ether and vinyl trimethoxysilane, which significantly improves its dispersibility and compatibility, and thus significantly improves the wear resistance, weather resistance and bending resistance of the cable.
[0088] 6) The performance comparison analysis of the materials of the outer protective sheath of the highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable prepared in Example 3 and Comparative Example 8 shows that in the preparation of the modified reinforced microspheres of the present application, dimethyldiindenylsilane, magnesium sulfate whiskers and mica powder are used to obtain a mica powder-loaded material, and then polyurethane is coated on the outside to obtain the modified reinforced microspheres. The magnesium sulfate whiskers have high strength, rigidity, wear resistance and weather resistance, and can increase the strength, wear resistance and rigidity of the outer protective sheath of the highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable. The dimethyldiindenylsilane and the other components of the outer protective sheath are fully Cross-linking forms a complete and tight network structure, so that the highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable can withstand greater force when subjected to external tensile stress, reduce the damage caused by stretching, and also have good weather resistance, effectively preventing the aging and degradation of the outer protective sheath. Mica powder is used for loading to achieve better dispersion effect, so that dimethylbisindenylsilane and magnesium sulfate whiskers can achieve synergistic effect while maintaining their unique properties, so that the outer protective sheath not only retains the stability, resilience and weather resistance of polyurethane, but also enhances the flame retardant effect, wear resistance and bending resistance.
[0089] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.
Claims
1. A highly wear-resistant, flame-retardant, weather-resistant and tensile drag chain cable, characterized in that: The invention comprises an outer protective sheath, wherein the outer protective sheath is prepared from raw materials including, by weight: 50-55 parts of nitrile rubber, 10-12 parts of polyvinyl chloride resin, 7-9 parts of polystyrene-polybutadiene-polystyrene copolymer, 4-6 parts of polyisobutylene, 3-4 parts of composite flame retardant, 20-22 parts of modified reinforced microspheres, 20-24 parts of modified nano titanium dioxide, 0.2-0.3 parts of ultraviolet absorber, and 1-2 parts of coupling agent, wherein the composite flame retardant is composed of graphene-modified 2-carboxyethylphenyl hypophosphite and rare earth flame retardant in a weight ratio of 5:3; The preparation method of the modified reinforced microspheres comprises the following steps: S51, according to the mass fractions, 1.5 parts of dimethylbisindenylsilane and 9 parts of ethanol were mixed to obtain a solution A, 3 parts of magnesium sulfate whiskers with a diameter of 3-5 μm and an aspect ratio of 10-12 and 5 parts of mica powder with a particle size of 5 microns were dispersed in 10 parts of deionized water to obtain a solution B, and the solution A was slowly added to the solution B, and after ultrasonic mixing, the solution was added to a hydrothermal reactor for treatment for 50-60 minutes. After the reaction was completed, the solution was filtered, washed, and dried to obtain a mica-loaded material; S52, according to the mass fractions, 6 parts of mica supported material were dispersed in 40 parts of ether to obtain solution C, 6 parts of polyurethane were dissolved in 30 parts of dichloromethane to obtain solution D, 0.07 parts of dibutyltin dilaurate were added to solution D, and then solution C was slowly added, after reacting for 6-7 hours, the solid was filtered out, washed, and vacuum dried at 130° C. to obtain modified reinforced microspheres; The preparation method of the graphene-modified 2-carboxyethylphenyl hypophosphorous acid comprises the following steps: S31, dispersing 100 parts of 2-carboxyethylphenylphosphite and 20 parts of graphene oxide in a solution consisting of 15 parts of γ-aminopropyltrimethoxysilane, 200 parts of ethanol and 25 parts of water according to parts by mass to obtain a mixed solution; S32, heating the mixed solution to 48°C, stirring at a rate of 500 rpm, reacting for 400 min, filtering, and vacuum drying at 73°C for 24 h, grinding and sieving to obtain graphene-modified 2-carboxyethylphenyl hypophosphorous acid with a particle size of 2-5 μm; The preparation method of the rare earth flame retardant is as follows: 4 mol of aminotrimethylenephosphonic acid and 1.5 mol of cerium nitrate are added into a hydrothermal reaction kettle, 200 mL of deionized water is added as a solvent, and 0.15 mol of lithium nitrate is added at the same time, and the temperature is raised to 155-165° C., and the reaction time is 30-36 hours to obtain the rare earth flame retardant; The preparation method of the modified nano titanium dioxide is as follows: according to the mass fraction, 10 parts of nano titanium dioxide are uniformly dispersed in 60 parts of anhydrous ethanol, and then 0.3 parts of hexamethyldisilazane, 0.2 parts of stearic acid, 0.15 parts of isomeric tridecanol polyoxyethylene ether, and 0.1 parts of vinyl trimethoxysilane are added, the temperature is maintained at 40° C., ultrasonic stirring is first performed for 50 minutes, ultrasonic cleaning is performed for 30 minutes, and magnetic stirring is performed for 3 hours, and then centrifugation, separation, washing, and drying are performed to obtain the modified nano titanium dioxide; The ultraviolet absorber is composed of dioctadecyl pentaerythritol phosphate and light stabilizer CHIMASSORB944 in a mass ratio of 3:4; The coupling agent is composed of vinyl trimethoxy silane and γ-glycidyloxypropyl trimethoxy silane in a mass ratio of 3:
4.
2. According to claim 1, a highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable, characterized in that: The acrylonitrile content of the nitrile rubber is 34-37%; the K value of the polyvinyl chloride resin is 63-65; the polyisobutylene is Oppanol B50 type, and the number average molecular weight is 340,000.
3. A method for preparing a highly wear-resistant, flame-retardant, weather-resistant and tensile-resistant drag chain cable as described in any one of claims 1-2, characterized in that: According to the mass proportions, nitrile rubber, polyvinyl chloride resin, polystyrene-polybutadiene-polystyrene copolymer, polyisobutylene, composite flame retardant, modified reinforcing microspheres, modified nano titanium dioxide, ultraviolet absorber and coupling agent are sequentially added into a high-speed mixer for premixing and mixing. The mixing temperature is 120-125°C for 30 minutes, and the mixture is cooled to 80°C. The mixture is then extruded and granulated through a twin-screw extruder. The extrusion temperature is 170-180°C and the screw speed is 120rpm to obtain the material for the outer protective sheath of the drag chain cable with high wear resistance, flame retardancy, weather resistance and tensile resistance.
Citation Information
Patent Citations
Wear-resistant oil-resistant flame-retardant drag chain cable and preparation method thereof
CN118126423A
Nbr composition and method for producing the same
JP2003335901A